(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Despite the scarcity of information on the archaeological contexts of Southwestern script, sufficient data exist to allow some characterisation of this phenomenon. The epigraphic remains appear clearly associated both with “cist” cemeteries and with those linked to tumuli. By contrast, such epigraphic manifestations are absent from the “enclosure” funerary universe and from the “Orientalising” pit burials. Acknowledging the differences between the material culture of the territory of the inscribed stelae and that of other areas—also reflected in settlement contexts—some cultural considerations are drawn regarding this dichotomy. Combining archaeological evidence with information from classical sources, the traditional association of this script with the Conii is questioned, and a stronger connection with the Celtics is preferred.